(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
This paper presents the first systematic account of calcareous algae from the limestones of the Lower Oligocene Gornji Grad beds of northern Slovenia. These bioclastic limestones are dominated by different coralline algal assemblages as well as corals, large and small benthic foraminifera as well as bivalves. The taxonomy and growth-forms of eleven species of seven non-geniculate coralline algal genera are described: Lithoporella, Neogoniolithon, Spongites, Lithothamnion, Mesophyllum, Sporolithon, Subterraniphyllum,. Additionally, the genera Polystrata (Peyssonneliaceae) Halimeda (Halimedaceae), and Cymopolia (Dasycladaceae) are present. The taxonomic interpretation of fossil coralline material in a manner consistent with generic and specific concepts currently in use for Recent material is, at present, difficult. In the absence of comparative studies on type material, only limited comparisons are possible, and in most cases definitive taxonomic conclusions cannot be reached. Most of the species designations are thus made following and open nomenclature, pending the rigorous taxonomic revision of historically established, fossil coralline algal species. The present study reveals a considerable variation of growth-form morphologies at both genus and species levels. This demonstrates the difficulties in using this feature as a diagnostic character in the identification of fossil coralline red algal taxa.